CURRENT CHALLENGES OF DIGITAL TRANSFORMATION AND THEIR IMPACT ON THE COMPETITIVENESS OF NATIONAL ECONOMIES - SHCHUPAKIVSKYI, ROMAN (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The importance of digitalization to ensure the competitiveness of the national economy is confirmed by world experience, according to which it can be assumed that the corresponding dependence will increase. Therefore, it is necessary to determine the priority areas of digital transformation, which should be subject to state regulation. The aim of the article is to substantiate the theoretical and methodological and applied characteristics of digital transformation (formation of information society, digitalization of economic relations and digitalization of the public environment) and its impact on the competitiveness of the national economy taking into account aspects of state regulation. According to the set goal, a number of results have been achieved, which can serve as a conceptual basis for studying the current challenges of digital transformation and their impact on the competitiveness of national economies. The essential and substantive characteristics of digitalization are generalized and it is emphasized that there is no established vision of this concept in the scientific discourse. The presence of both multilevel and functional approaches to the semantic characteristics of digitalization is proved. The key channels (business, society, country) of dissemination of essential provisions of digital transformation of economy are noted. Examining the institutional and legal framework for the regulation of digitalization in Ukraine, it was found that its basic components in our country include the real sector of the economy and society. Modern trends of digitalization are substantiated through the prism of three vectors of its distribution - the formation of the information society, digitalization of economic relations and digitalization of the public environment. The consequences of digitalization in the field of economic competitiveness and its state regulation are identified. It is concluded that the current challenges of digital transformation provide both better opportunities and create new threats to society’s progress and increase the competitiveness of national economies. Emphasis is placed on the need for constant monitoring of current digitalization trends in order to preserve and realize the country’s own competitive potential.